Novel browser extension tool for image annotation : (Applications and use-cases in a novel CCTV-aware system) - Lahtinen, Tuomo (2022)
Camera surveillance has become a worldwide phenomenon that affects the lives of almost every person. People are not aware of how much they are entering the surveillance zone and for some people the patronizing surveillance may raise concerns about individual freedom and privacy. This paper introduces a browser extension that allows users to annotate cameras to build a security / privacy type of navigation that avoids or follows cameras. Image annotation started with describing images with words that have evolved to annotate images in more detail, and today large datasets can be used for ML/CV model training. The purpose of the browser extension was to annotate images in a way that training of ML/CV models to recognize CCTV cameras from Google Street View images is possible. The browser extension was tested with the crowdsourcing effort where eight different people used the extension in different browsers and different operating systems, after which the people evaluated the extensions functionality and ease of use. The evaluation showed that the extension works as indented and it is an effective tool for annotating images. In addition, the extension succeeded in training ML/CV models to recognize CCTV cameras from Street View-level images.